2020
DOI: 10.1017/s0714980820000173
|View full text |Cite
|
Sign up to set email alerts
|

Let’s Work Together: Assessing the Impact of Intergenerational Dynamics on Young Workers’ Ageism Awareness and Job Satisfaction

Abstract: Previous studies suggest that intergroup contact has a positive effect on older workers’ perception of ageism and satisfaction. This study aims at assessing such relationships amongst Canadian younger workers. Precisely, in light of the intergroup contact theory (ICT), it was first hypothesized that a positive perception of intergenerational workplace climate (IWC) and knowledge sharing practices (KSP) increase younger workers’ awareness of ageist behaviors targeting older peers. Second, it was hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
1
3
1
Order By: Relevance
“…When factor-based correlations for the three factors were correlated with life satisfaction, ageism was the only variable that correlated significantly. The result that climate and job engagement were not predictive of life satisfaction was contrary to our expectation based on earlier studies [21,31,[34][35][36]. Furthermore, when life satisfaction was regressed on demographic variables, R 2 was not significant, but when the three factors were added in the second step, the change in R 2 reached marginal significance.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…When factor-based correlations for the three factors were correlated with life satisfaction, ageism was the only variable that correlated significantly. The result that climate and job engagement were not predictive of life satisfaction was contrary to our expectation based on earlier studies [21,31,[34][35][36]. Furthermore, when life satisfaction was regressed on demographic variables, R 2 was not significant, but when the three factors were added in the second step, the change in R 2 reached marginal significance.…”
Section: Discussioncontrasting
confidence: 98%
“…Considering the results of the correlational analysis, as expected given prior studies [20,21], individuals who reported more age-related discrimination and age-related meta-stereotypes expressed lower life satisfaction. Moreover, respondents who were more emotionally engaged with their jobs were more likely to express greater life satisfaction.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Since the WICS was introduced in 2017, a total of 27 journal articles citing this scale have been published ( Web of Science, January 6, 2023). About two thirds of these (19 out of 27) were published in management or gerontology journals; and many of them focused on understanding factors and consequences associated with age-diversity climate such as feelings of satisfaction at work or work engagement (e.g., Lagacé et al, 2019 ; Firzly et al, 2021 ; McConatha et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%